Constitutional Investigations : A Conversation with Linda Colley. - Burton, Howard (Open Agenda Publishing, 2021)
This book is based on an in-depth filmed conversation between Howard Burton and Linda Colley, the Shelby M.C. Davis 1958 Professor of History at Princeton University. Linda Colley is a renowned expert on British, imperial and global history since 1700. After inspiring insights about Linda Colley's teachers and professors who had a strong impact on her future career as a historian, this wide-ranging conversation provides a detailed examination of the global history and present state of constitutions and their impact.This carefully-edited book includes an introduction, Knowing the Rules, and que.
Description based upon print version of record.
Keywords: Constitutional history.; Constitutions.; Constitutional law.; Histoire constitutionnelle.; Droit constitutionnel.; constitutions.; World.; HISTORY.; POLITICAL SCIENCE.; LAW.; Constitutional history; Constitutional law; Constitutions